2020
DOI: 10.7824/rbh.v19i2.688
|View full text |Cite
|
Sign up to set email alerts
|

Estudo De Seleção Da Comunidade Infestante Por Herbicidas Utilizando Técnicas De Análise Multivariada

Abstract: Para a tomada de decisão sobre qual estratégia é melhor para manejo de plantas daninhas podem ser usadas ferramentas estatísticas, como análise multivariada, principalmente quando se dispõe de quantidade elevada de dados. Assim, objetivou-se avaliar a viabilidade da utilização da análise multivariada para estudos de seleção da flora de plantas daninhas em decorrência da aplicação de diferentes herbicidas. O experimento foi conduzido em campo, em delineamento experimental blocos ao acaso, com quatro repetições,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…At 108 DAA of the treatments, it is observed that the species COMBE and ALTTE, similar to the first evaluation, showed high values of RI with 29.90 and 24.22, respectively, followed by CONBO, with 11.51. Such species present a high RI value in Brazilian agriculture, which is difficult to control and has high dissemination (Ribeiro Neto et al, 2019;Miranda et al, 2020). Biological characteristics such as propagation, life cycle, high seed production, and easy adaptation, among others, can justify the importance of these species in the study area.…”
Section: Resultsmentioning
confidence: 99%
“…At 108 DAA of the treatments, it is observed that the species COMBE and ALTTE, similar to the first evaluation, showed high values of RI with 29.90 and 24.22, respectively, followed by CONBO, with 11.51. Such species present a high RI value in Brazilian agriculture, which is difficult to control and has high dissemination (Ribeiro Neto et al, 2019;Miranda et al, 2020). Biological characteristics such as propagation, life cycle, high seed production, and easy adaptation, among others, can justify the importance of these species in the study area.…”
Section: Resultsmentioning
confidence: 99%